Bacteria in agrobiology plant nutrient management - Maheshwari, Dinesh K.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
The future of agriculture strongly depends on our ability to enhance productivity without sacrificing long-term production potential. An ecologically and economically sustainable strategy is the application of microorganisms, such as the diverse bacterial species of plant growth promoting bacteria (PGPB). The use of these bio-resources for the enhancement of crop productivity is gaining worldwide importance. ?Bacteria in Agrobiology: Plant Nutrient Management? focus on the management of plant nutrient to support plant growth and development. The topics treated in this book include mechanisms of plant growth promoting rhizobacteria, zinc and phosphate solubilizing microorganisms, sulfur oxidizing bacteria, ACC deaminase, siderophores, phytohormones, quorum-sensing, biofilms, antibiotics, volatiles, denitrification and integrated nutrient management
Maheshwari, DK: Role of PGPR in Integrated Nutrient Management of Oil Seed Crops -- Gamalero, E:Mechanisms Used by Plant Growth-Promoting Bacteria -- Sa, TM:Microbial Zinc Solubilization and their Role on Plants -- Osorio, NW: Effectiveness of Phosphate solubilizing Microorganism in Increasing Plant Phosphate Uptake and growth in Tropical Soils -- Sa, TM:Sulfur Oxidizing Bacteria: A Novel Bio-inoculant for Sulfur Nutrition and Crop Production -- Desai, A:  Role of Siderophores in Crop Improvement -- Cassán, F:Basic and Technological Aspects of Phytohormone Production by Microorganisms: Azospirillum sp. as a Model of Plant Growth Promoting Rhizobacteria -- Annapurna, K:ACC Deaminase Containing PGPR for Potential Exploitation in Agriculture -- Chernin,LS: Quorum-sensing Signals as Mediators of PGPRs' Beneficial Traits -- Mathivanan, N: Management Of Plant Diseases By Microbial Metabolites -- Mavrodi, DV: The Role of 2,4-diacetylphloroglucinol- and phenazine-1-carboxylic acid-producing Pseudomonas spp. in Natural Protection of Wheat from Soilborne Pathogens -- Timmusk, S:Plant root associated biofilms: perspectives for natural product mining -- Fernando, WGD: Bacterial, Fungal and Plant Volatile Compounds in Reducing Plant Pathogen Inoculums -- Fernández,LA: Denitrification Activity in Soils for Sustainable Agriculture
Title from title screen (viewed September 25, 2023)
Electronic reproduction
Keywords: Plant growth-promoting rhizobacteria; Crops -- Nutrition; Plant nutrients